SUCCESS FACTORS IN THE ACCOUNTING INFORMATION QUALITY (SURVEY AT PT. PRIVATE PLANTATION IN PALEMBANG CITY) - Ladewi, Yuhanis; Dina Aziza Putri; Lis Djuniar; Nunung Nurhayati (UPT Publikasi Ilmiah UNISBA, 2024)
This study aims to determine and partially analyze the effect of internal control, data quality, and accounting information system quality on accounting information quality. Data testing is about validity and reliability. Data analysis techniques include descriptive and inferential statistics. Based on the number of questionnaires returned and processed, as many as 33 respondents showed that all of them were valid and reliable. Descriptive statistical analysis per variable shows the dominant value is very high. The results of inferential statistics show that the results of residual values are normally distributed; multicollinearity and heteroskedasticity do not occur. Multiple linear regression tests show that if internal control variables, data quality, and accounting information system quality are considered constant, then the quality of accounting information will increase. The results of research on the t test show that partially internal control, data quality, and accounting information system quality affect accounting information quality. Keywords : Success Factors, Accounting Information Quality.